2022
DOI: 10.7150/ijms.71931
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of EZH2 Genetic Variants on Triple-Negative Breast Cancer Susceptibility and Pathology

Abstract: Triple-negative breast cancer (TNBC) is the third most common female cancer in Taiwan. EZH2 plays an important role in cancer development through transcriptional repression by chromatin remodeling. However, the expression of EZH2 in breast cancer is highly correlated with tumorigenesis, and patient survival is not matched to TNBC. Furthermore, it has not been determined if specific EZH2 genetic variants are associated with breast cancer risk. In this paper, we evaluated the survival of different types of breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…It is known that along with the impact of environmental factors, genetic pre-disposition plays an important role in the epigenetic changes associated with various pathologies [39,46]. Numerous examples of different pathologies related to genetic variation (SNPs) underlying the abnormalities in the expression or function of the genes coding for epigenetic factors, including histone acetylases [99,100], deacetylases [101][102][103], histone methyltransferases [102,104], and components of chromatin remodeler complexes [105,106], have been thus far accumulated. However, most of these results have been obtained when studying different types of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that along with the impact of environmental factors, genetic pre-disposition plays an important role in the epigenetic changes associated with various pathologies [39,46]. Numerous examples of different pathologies related to genetic variation (SNPs) underlying the abnormalities in the expression or function of the genes coding for epigenetic factors, including histone acetylases [99,100], deacetylases [101][102][103], histone methyltransferases [102,104], and components of chromatin remodeler complexes [105,106], have been thus far accumulated. However, most of these results have been obtained when studying different types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these results have been obtained when studying different types of cancer. For example, two SNPs (rs6950683 and re3757441) of EZH2 coding for the histone methyltransferase that causes the trimethylation of H1K26 and, consequently, suppresses the cancer preventive genes were shown to be associated with a tumor size in triple-negative breast cancer [102]. Further, the association-based study of SNP rs201135441C>T shows that the T allele of rs201135441 significantly increases the risk of breast cancer susceptibility and reduces the overall survival rate [107].…”
Section: Discussionmentioning
confidence: 99%
“…17 Given the importance of PRC2 in the development and progression of many tumors, genetic variants within PRC2 have been implicated in susceptibility to different cancers, including prostate 22 and triple-negative breast cancer. 23 A previous study reported that the C/C genotype of rs6950683 and the C/C genotype of rs3757441 in EZH2 reduced susceptibility to oral squamous cell carcinoma. 24 Additionally, Hyuna Sung et al 25 identified a protective effect of the T variant at the rs10898459 site in EED against esophageal squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 98%
“…Genetic and epigenetic alterations in TNBC are some of the main obstacles for successful responses to therapy [7]. Among the TNBC markers identified as potential therapeutic targets, the methyltransferase enhancer of zeste homolog 2 (EZH2) holds significant promise, as its overexpression is associated with poor prognosis and short disease-free survival in patients [8][9][10][11]. This may occur in part through the increased stability of EZH2 due to upstream regulatory pathways leading to its post-translational modification in aggressive TNBCs [12].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we probed the role of EZH2 in primary and metastatic TNBCs [18] using a 4T1 murine TNBC model. EZH2 was previously shown to be significantly upregulated in 4T1 compared to normal mouse breast epithelial cells [10]. To this end, we used CRISPR technology to drive EZH2 gene knockout (KO) and overexpression (OE) in stable cell lines derived from parent wild-type (WT) 4T1 cells, resulting in EZH2 protein KO and OE, respectively.…”
Section: Introductionmentioning
confidence: 99%